2018
DOI: 10.3390/magnetochemistry5010002
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Spin Manipulation of Nickel-Quinonoid Complex Adsorbed on Co(001) Substrate

Abstract: We studied the structural, electronic, and magnetic properties of a recently synthesized Ni(II)-quinonoid complex upon adsorption on a magnetic Co(001) substrate. Our density functional theory + U (DFT+U) calculations predict that the molecule undergoes a spin-state switching from low-spin S = 0 in the gas phase to high-spin S ≈ 1 when adsorbed on the Co(001) surface. A strong covalent interaction of the quinonoid rings and surface atoms leads to an increase of the Ni–O(N) bond lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… 9 In one of our previous report, we have shown that the Ni-quinonoid molecule chemisorbed on the Co(100) surface, coupled ferromagnetically with the substrate, in which the Ni spin state switches from low spin (LS) to high spin (HS). 10 Several quinonoid-based organometallic compounds have been synthesized in the past few years, aiming to their application in spintronics. Kar et al 11 have recently reported quinonoid-based homo- and hetero-dinuclear complexes, where the two noble metals (Pt II and/or Pd II ) are linked through a quinonoid molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In one of our previous report, we have shown that the Ni-quinonoid molecule chemisorbed on the Co(100) surface, coupled ferromagnetically with the substrate, in which the Ni spin state switches from low spin (LS) to high spin (HS). 10 Several quinonoid-based organometallic compounds have been synthesized in the past few years, aiming to their application in spintronics. Kar et al 11 have recently reported quinonoid-based homo- and hetero-dinuclear complexes, where the two noble metals (Pt II and/or Pd II ) are linked through a quinonoid molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a multifunctional Ni-quinonoid molecule has been reported in which a Ni atom connects two quinonoid molecules, exhibits a reversible color change, and undergoes structural transformation upon methanol adsorption . In one of our previous report, we have shown that the Ni-quinonoid molecule chemisorbed on the Co(100) surface, coupled ferromagnetically with the substrate, in which the Ni spin state switches from low spin (LS) to high spin (HS) . Several quinonoid-based organometallic compounds have been synthesized in the past few years, aiming to their application in spintronics.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth understanding of the electronic structure and magnetic properties of surface-adsorbed organic molecules is of direct relevance for and key to molecular spintronics [1][2][3][4][5][6][7][8][9][10][11]. Naturally, the deposition of nonmagnetic, closedshell molecules on magnetic substrates can result in a magnetic polarization of the molecule [12][13][14][15][16][17]. Conversely, for molecules which are already spin polarized in the gas phase, adsorption on a nonmagnetic surface can also result in interesting molecular magnetic properties, e.g., via charge-transfer processes from/towards the molecule and screening effects [16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, the deposition of nonmagnetic, closedshell molecules on magnetic substrates can result in a magnetic polarization of the molecule [12][13][14][15][16][17]. Conversely, for molecules which are already spin polarized in the gas phase, adsorption on a nonmagnetic surface can also result in interesting molecular magnetic properties, e.g., via charge-transfer processes from/towards the molecule and screening effects [16,[18][19][20][21]. The intrinsic magnetic moment of molecules is often quenched upon adsorption, especially in the case of strong hybridization [22][23][24].…”
Section: Introductionmentioning
confidence: 99%